2017
DOI: 10.1002/mus.25950
|View full text |Cite
|
Sign up to set email alerts
|

Urate levels predict survival in amyotrophic lateral sclerosis: Analysis of the expanded Pooled Resource Open‐Access ALS clinical trials database

Abstract: Our pooled analysis provides further support for urate as a prognostic factor for survival in ALS and confirms the utility of the PRO-ACT database as a powerful resource for ALS epidemiological research. Muscle Nerve 57: 430-434, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…This result is in line with prior studies demonstrating that higher levels of urate are associated with a lower risk 25 and slower progression in ALS. 26,27 None of the metabolites in the 16 pathways most commonly reported to be altered in previous studies, which included the metabolism of several amino acids, caffeine metabolism, aminoacyl RNA biosynthesis, and pantothenate and CoA biosynthesis, 2 were associated with ALS risk after we accounted for multiple comparisons. The inconsistent results are likely because of the different study designs, where our study evaluated the association between the prediagnostic metabolomic profile and ALS risk, while all of the previous studies compared the metabolome in patients with ALS with controls.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in line with prior studies demonstrating that higher levels of urate are associated with a lower risk 25 and slower progression in ALS. 26,27 None of the metabolites in the 16 pathways most commonly reported to be altered in previous studies, which included the metabolism of several amino acids, caffeine metabolism, aminoacyl RNA biosynthesis, and pantothenate and CoA biosynthesis, 2 were associated with ALS risk after we accounted for multiple comparisons. The inconsistent results are likely because of the different study designs, where our study evaluated the association between the prediagnostic metabolomic profile and ALS risk, while all of the previous studies compared the metabolome in patients with ALS with controls.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were ALS patients at greater risk of clinical progression based on having serum urate levels below the population median of 5.5 mg/dL. [17][18][19][20][21][22] In this population, treatment with inosine was safe and well tolerated at doses that elevated serum urate concentrations from a mean of 4.1 mg/dL to target levels of 7 to 8 mg/dL.…”
Section: Discussionmentioning
confidence: 99%
“…In ALS observational studies, high urate levels are predictive of improved survival. [17][18][19][20][21][22][23] Whether these associations reflect a causal protective role of urate is unknown though growing evidence supports urate as a neuroprotectant in several models of neurodegeneration, including a cellular model of ALS. 12,[27][28][29][30][31][32]45 In this pilot trial, the addition of biomarkers to track oxidative (and closely related nitrosative) 13,46 stress and damage supported the biologically relevant effects of inosine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that serum UA is reduced in patients with neurodegenerative disorders such as PD (Havelund et al, 2017; Sakuta et al, 2017; Wen et al, 2017), ALS (Abraham and Drory, 2014; Paganoni et al, 2018; Zhang et al, 2018), and AD (Euser et al, 2009; Lu et al, 2016), and as mentioned above, many researchers consider that these observations represent a direct protective role of UA suppressing ROS in the brain (Kori et al, 2016). However, since XOR is not expressed in the brain, and UA levels in the brain are naturally very low, it is more likely that low UA in neurodegenerative disorder patients reflects physiologic and biochemical changes that result in decreased energy production and low ATP consumption.…”
Section: Cellular Energy-charge and Atp Turnovermentioning
confidence: 94%